1993
DOI: 10.1161/01.hyp.21.5.731
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of plasma immunoglobulin A in the spontaneously hypertensive rat.

Abstract: Prior studies describe deficiencies of T-cell-mediated immunity in the spontaneously hypertensive rat (SHR) strain of Okamoto and Aoki. This report describes an alteration of humoral immunity: elevation of the plasma concentration of immunoglobulin (Ig) A and of circulating IgA autoantibodies to single-stranded DNA, double-stranded DNA, and thyroglobulin. The increased plasma IgA levels are evident in prehypertensive SHR, hence not secondary to the hypertension, and they result mainly from increments in polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
2
16
1
Order By: Relevance
“…The results of the present study are in agreement with the data reported elsewhere for hypertensive humans and animals, [1][2][3][4][5][6][7][8][9][10][23][24][25][26][27] and demonstrate that plasma Fb concentration was increased in SHRs compared to the normal level of about 3 mg/mL in WKY rats. This significantly higher concentration of Fb (4 mg/mL) may be a factor in the increased RBC aggregation in homologous plasma in hypertensive rats (Results; 25).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of the present study are in agreement with the data reported elsewhere for hypertensive humans and animals, [1][2][3][4][5][6][7][8][9][10][23][24][25][26][27] and demonstrate that plasma Fb concentration was increased in SHRs compared to the normal level of about 3 mg/mL in WKY rats. This significantly higher concentration of Fb (4 mg/mL) may be a factor in the increased RBC aggregation in homologous plasma in hypertensive rats (Results; 25).…”
Section: Discussionsupporting
confidence: 93%
“…Alterations of major determinants of the blood's rheological properties observed in hypertensive disease include increased viscosity of blood [23,24] and plasma, [23][24][25] increased hematocrit [24,25] and increased levels of high molecular weight plasma proteins including fibronectin, [25] immunoglobulin-A [26] and particularly fibrinogen (Fb), [3] which are the major determinants of plasma viscosity. Furthermore, it has been shown that RBC aggregation, which has the most significant effect on blood rheological properties, is increased during hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Similarly, in spontaneously hypertensive rats, a series of disturbances of the humoral and cellular immune response are present. 6 Interleukin-6 (IL-6) is an important component of the pro-inflammatory response and may be secreted by several tissues and cell types, including monocytes and macrophages, T and B-cells, fibroblasts, bone marrow stromal cells, endothelial cells, hepatocytes, smooth muscle cells, and adipose tissue. 7 IL-6 plays a key role in driving the acute inflammatory response and orchestrates the production of acute phase proteins.…”
Section: Introductionmentioning
confidence: 99%